Ferns and lycophytes from Rancho Souza, municipality of Abaetetuba, Pará State, Brazil (Research, Society and Development, 2022)
This work presents a floristic survey of the ferns and lycophytes from Rancho Souza, municipality of Abaetetuba, Pará State, Brazil, with identification key to species and information on their habit, life form, occurring environment and pattern of geographical distribution. In the study area, 31 species of seedless vascular plants were recorded, being one lycophyte (Selaginella conduplicata Spring, Selaginellaceae) and 30 ferns, distributed in 22 genera and 14 families. The most representative families were Pteridaceae (6 spp.), Hymenophyllaceae (4 spp.) and Polypodiaceae (4 spp.). The genera with highest species richness were Cyathea J. Sm. (3 spp.) e Didymoglossum Desv. (3 spp.). The majority of the species have herbaceous habit (26 spp.), terrestrial (17 spp.) and epiphytic (12 spp.) life forms, American distribution (25 spp.), and inhabit the forest interior (24 spp.). These results demonstrate the importance of preserving forest remnants in areas under strong anthropic pressure for the conservation of regional ferns and lycophytes flora.